RESPON PERTUMBUHAN VEGETATIF TANAMAN PADI PADA BERBAGAI DOSIS PUPUK ORGANIK DAN JUMLAH BIBIT PER LUBANG TANAM - Muhammad Jalil; Jekki Irawan (Universitas Teuku Umar, 2018)
This research aimed to know the effect of organic fertilizer dose and number of seed per hole towards growth of rice and real or no interaction of both factors. This research used split plot experimental design 4 x 3 with 3 replication. The first factor of this research is dose of organic fertilizer as main plot consist of 0, 5, 10 and 15 ton/ha. And the second factor is number of seed per hole as subplot, consist of 1, 2 and 3 per hole. This research was conducted at Lhok Rameuan village, Suka Makmue districts, Nagan Raya regency of Aceh Province on Juny until December 2016. The result showed that dose of organik fertilizer influenced significantly on high of plant and number of tillers in 3 weeks after plant. Significant effect on high of plant in 2 and 4 weeks after plant and number of tiller on 4 weeks after plant, but not significant on number of seed on age 2 weeks after plant. Number of plant per hole influenced significantly effect on high of plant an number of tillers on age 2 and 3 weeks after plant, but not significant on high an number of tiller on 4 weeks after plant. Statistical analysis showed no interaction occured between both factors treated on all observation variabels./